Endoscopic Management of Congenital Middle Ear Ossicular Chain Anomalies: A Multicenter Study - Orhan, Kadir Serkan; Celik, Mehmet; Ozdek, Ali; Gulsen, Secaattin; Yorgancilar, Ediz; Surmelioglu, Ozgur; Guneri, Enis Alpin (Lippincott Williams & Wilkins, 2026)
Objective: This study evaluates the surgical and audiological outcomes of transcanal endoscopic ear surgery (TEES) in patients with congenital ossicular chain anomalies (COCAs) using the Teunissen-Cremers classification system. Study design: Multicenter, retrospective clinical study. Setting: Tertiary referral centers with experienced endoscopic ear surgeons. Patients: A total of 51 patients were diagnosed with COCAs and treated with TEES. Patients with chronic otitis media, cholesteatoma, tympanosclerosis, otosclerosis, or those requiring microscopic/endaural/retroauricular approaches were excluded. Intervention: Transcanal endoscopic ossicular chain reconstructions were performed using various techniques, including stapedotomy, partial and total ossicular prosthesis or autologous bone or cartilage graft placements, and bone cement bridging. Main outcome measures: Air-bone gap (ABG) closure, operation duration, hospital stay, and postoperative complications. Results: The mean preoperative ABG was 42.5 +/- 10.9 dB HL, which improved to a mean postoperative ABG of 20.3 +/- 12.3 dB HL, yielding a mean ABG closure of 22.3 +/- 12.2 dB HL. Patients classified as Class 1, 2, and 3 demonstrated significantly greater ABG closure rates compared with Class 4 cases ( P <0.059). The mean surgical duration was 72.1 +/- 19.9 minutes, and the mean hospital stay was 29.6 +/- 15.3 hours. No intraoperative or immediate postoperative complications were observed. Five patients required revision surgery due to recurrent conductive hearing loss. Conclusions: TEES is a safe and effective technique for managing COCAs, offering significant ABG improvement, particularly in Class 1 to 3 anomalies. The minimally invasive nature of TEES, combined with superior exposure and visualization, results in favorable audiological outcomes with minimal complications and reduced hospital stay.
Keywords: Air-bone gap closure; Congenital ossicular chain anomaly; Hearing outcomes; Ossicular chain reconstruction; Ossiculoplasty; Transcanal endoscopic ear surgery